Philippine government adopts CCAFS outputs and inputs in reviewing, developing, and implementing climate-smart agriculture-related policies and programs - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Outputs and recommendations developed by CCAFS were used by key Philippine government agencies (specifically the Department of Agriculture[DA]) in reviewing, developing, and implementing national policies and key programs, including the Rice Competitiveness Enhancement Fund(RCEF). Through RCEF, the Philippine government allotted PhP60B (USD1.2B) for climate-smart rice production, targeting 1.89 million rice farmers in 57 provinces of the country. Since the RCEF implementation in 2020, CCAFS innovations (i.e., Climate-Smart Village, school-on-the air) are being used as platforms for implementing the program's components.